Palladium-Catalyzed Direct Acylation: One-Pot Relay Synthesis of Anthraquinones - Suchand, Basuli; Satyanarayana, Gedu (Synthesis, 2019)
A bis-acylation strategy to access functionalized anthraquinones via one-pot relay process, is presented. The first acylation was feasible under [Pd]-catalyzed intermolecular direct acylation reaction, while, the second acylation was accomplished by using intramolecular Friedel–Crafts acylation. Notably, benchtop aldehydes have been utilized as non-toxic acylation agents in the key [Pd]-catalyzed acylation.
Keywords: anthraquinone; catalysis; acylation; one-pot; Friedel–Crafts acylation